Comparative health risk assessment of realgar and NiuHuangJieDu tablets based on tissue arsenic levels after multiple oral administration to rats. (1st March 2020) - Wu, Xiao; Guan, Rong; Liu, Yuexin; Wu, Shanhu; Song, Min; Hang, Taijun
Abstract: Ethnopharmacological relevance: Realgar (As2 S2 ), a mineral traditional Chinese medicine (TCM), is proved to have great therapeutic effects in clinic and has been widely used in China for hundreds of years. As one of the most popular realgar-containing TCMs, NiuHuangJieDu Tablets (NHJDT) is used as OTC (over-the-counter) drug in daily life for fever relieving, detoxicating, as well as cure of sore throat and gingival swelling. However, the safety of realgar and its-containing TCMs still remains unclear. Aim of the study: This study was to investigate the accumulation of arsenic in rat body and evaluate the safety of realgar-containing TCMs in vivo . Materials and methods: The health risk of arsenic was evaluated in rats by tissue distribution and histopathology, as well as arsenic speciation in plasma after multiple oral gavage of low and high doses of realgar and NiuHuangJieDu Tablets (NHJDT), respectively. Total arsenic and arsenic speciation were determined by hydride generation–atomic fluorescence spectrometry (HG-AFS) and high performance liquid chromatography–hydride generation–atomic fluorescence spectrometry (HPLC-HG-AFS), respectively. Results: Arsenic accumulated in rat tissues especially in heart, liver, spleen, lung, kidney, uterus and ovary. Dimethylarsenic acid (DMA) was detected as the predominant species in rat plasma after dosing. In comparison of realgar, NHJDT with co-existing components significantly alleviated tissues injury, and reduced arsenic concentration in rat tissues and plasma. Conclusions: NHJDT with co-existing components combination was relatively safer than realgar, but the accumulation of arsenic was still significant after long-term medication. Therefore, great attentions should be paid to realgar-containing TCMs to avoid toxicity from arsenic accumulation. Moreover, the dose regimen of realgar-containing TCMs should be designed rationally for clinical application. These results may provide useful references for the application of realgar-containing TCMs and might be helpful for the understanding of TCM compound compatibility. Graphical abstract: Image 1